Psikologi Pendidikan Anak dalam Al-Qur’an Perspektif Wahbah Az zuhaili dalam Tafsir Al-Munir - Lubis, Muhammad Jihad Azni; Zuhri, Ahmad; Daulay, Nurussakinah (Jurnal Ragam Pengabdian, 2026)
This article examines the Qur'anic framework for children's development from dependents requiring parental care and protection into individuals capable of exercising moral agency and ethical responsibility. It addresses a tendency in Islamic parenting scholarship to emphasize parental obligations, protection, discipline, and obedience without adequately integrating children's developing capacities, privacy, self-regulation, value internalization, and the gradual transfer of responsibility into a coherent conceptual framework. The study aims to explain this developmental process and interpret isti'dhān as part of forming children's awareness of interpersonal boundaries and moral agency. It employs a qualitative textual design combining thematic-conceptual Qur'anic interpretation with qualitative content analysis, focusing on Q.S. al-Baqarah [2]: 233, Q.S. al-Nūr [24]: 58–59, and Q.S. Luqmān [31]: 12–19, analyzed through textual, contextual, and intratextual readings, thematic coding, and engagement with theories of moral development, privacy, and child agency. Findings identify four interconnected dimensions of Qur'anic parenting: relational protection and fulfillment of children's needs, habituation in respecting privacy and interpersonal boundaries, transformation of obedience into moral internalization, and formation of agency through self-regulation and social responsibility. The study conceptualizes Qur'anic moral agency as a relational, gradual, and accountable capacity grounded in trust, welfare, dignity, and responsibility before God, contributing a unified Qur'an-based model integrating parenting, privacy, capacity development, and ethical responsibility.